Identification of Novel Rho-Kinase-II Inhibitors with Vasodilatory Activity - Kesar, Seema (ACS Med Chem Lett, 2020)
[Image: see text] Small GTPase protein Rho-kinase (ROCK) plays an important role in the pathogenesis of hypertension. Inhibition of ROCK II brings about the biochemical changes leading to vascular smooth muscles relaxation, finally resulting into potent antihypertensive activity. In the quest for potent ROCK-II inhibitors, a ligand-based pharmacophore containing four essential chemical features, namely two hydrogen bond acceptor (HBA), one hydrogen bond donor (HBD), and one hydrophobe (HY), was developed and rigorously validated. The pharmacophore was used for virtual screening, and hits retrieved from the National Cancer Institute (NCI) database were sorted on the basis of fit value, estimate value, and Lipinski’s violation. Potential feature interaction of hits was also observed during docking studies with the amino acids present in the active site of Rho-kinase. Based on the above screening, three hits (NSC 2488, NSC 2888, and NSC 4231) were chosen and subjected to in vitro Rho-kinase enzyme-based assay, followed by ex vivo rat aortic vasodilatory assay. All three compounds showed good biological activity as predicted by the model and confirmed by the docking studies.